Impact of cervical cancer on quality of life of women in Hubei, China - Niresh Thapa (2018)
© 2018, The Author(s). We aimed to assess the quality of life (QOL) of the patients with cervical cancer after initial treatment, the factors affecting QOL and their clinical relevance. A total of 256 patients with cervical cancer who visited Zhongnan Hospital of Wuhan University from January 2017 to December 2017 were enrolled in this study. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 item (EORTC QLQ-C30) and cervical cancer module (EORTC QLQ-CX24) was used to assess the QOL of patients. More than half of the patients with cervical cancer reported an excellent QOL. Symptoms mostly experienced were insomnia, constipation, financial difficulties, and menopausal symptoms. Global QOL and social functioning were statistically associated with education level, occupation, the area of living, family income and treatment modality. Similarly, role functioning showed significant association with the stage of cancer, treatment modality and time since diagnosis. The rural area of living and poor economic status of the patients with cervical cancer has a negative impact on overall quality of life. Younger and educated patients are more worried about sexuality. Patients treated with multiple therapies had more problems with their QOL scales than patients treated with surgery only.